Evaluation of the Optic Nerve Head in Patients with Pseudoexfoliation Syndrome - Hong Anh, Trinh; Thi Van Anh, Bui; Truong Khanh Van, Tham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4DO - 10.25073/2588-1132/vnumps.4862, 2025)
Abstract: Patients and Methods: A cross-sectional descriptive study was conducted on 28 patients (41 eyes) diagnosed with pseudoexfoliation syndrome. All subjects underwent visual acuity testing, intraocular pressure measurement, clinical examination, and SS-OCT imaging to assess the lamina cribrosa structure and optic nerve head vessel density. The collected parameters included lamina cribrosa thickness, lamina cribrosa depth, lamina cribrosa curvature index, prelaminar tissue thickness, and vessel density in superficial and deep layers, which were recorded and statistically analyzed using SPSS 22.0. Results: The mean age of the study group was 74.8 ± 6.9 years, and 64.3% were male. The thickness and structural parameters of the lamina cribrosa were as follows: lamina cribrosa thickness (LCT) = 216.26 ± 49.02 µm, lamina cribrosa depth (LCD) = 443.60 ± 104.13 µm, lamina cribrosa curvature index (LCCI) = 8.23 ± 2.49, and prelaminar tissue thickness (PLTT) = 188.43 ± 78.38 µm. Superficial vessel density in the central region (37.67 ± 12.31%) was markedly lower than in the parapapillary (49.20–54.08%) and peripapillary regions (42.12–44.08%). At the deep layer, vessel density in the central, parapapillary, and peripapillary regions was 42.98 ± 14.68%, 51.26–57.60%, and 49.95–50.94%, respectively. Conclusion: Patients with pseudoexfoliation syndrome exhibited morphological alterations of the lamina cribrosa and a significant reduction in optic nerve head vessel density, particularly in the superficial layer and central region. Keywords: Pseudoexfoliation syndrome, pseudoexfoliative glaucoma, ocular hypertension, optic nerve head, SS-OCT Triton, lamina cribrosa.